PEGELOLAAN DATA DAN HISTORI PENGGUNA UNTUK PENGEMBANGAN SISTEM INFORMASI BERKAH BERSAMA BERBASIS WEBISTE - Sefhia Febriana Budiarti; Billy Sabella; Khairul Anwar Hafizd (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
The Berkah Bersama Information System is an information system for manage various data of division general and finance, logistics, also production and marketing used in the Berkah Bersama Company. However, there are still some data management that are not yet included in the system and are still carried out computerized but not integrated through Microsoft Excel. Some of these data include data recording, RHPP (Daily Recapitulation of Farmer Maintenance), drug programs, chick in profit and loss, and user history. So, it is necessary to develop so that data management in the system becomes more complex. This research uses an incremental model, ERD (Entity Relationship Diagram), UML (Unified Modelling Language), and uses the CodeIgniter framework. The results of this research are in the form of Data Management and User History for the Development of a Website-Based Berkah Bersama Information System which useful for managing user data and history. System testing is carried out using the Black-Box Testing method, and the system run according to its functions.